Mooseltoe - Palatini, Margie; Cole, Henry, 1955- (New York : Scholastic Inc., 2001)
Moose thinks he has all his Christmas preparations taken care of, but at the last minute he must come up with a substitute for the Christmas tree.
Originally published: New York : Hyperion Books for Children, 2000.
180
Keywords: Christmas -- Fiction; Christmas trees -- Fiction; Moose -- Fiction; Mustaches -- Fiction